Spatial filter with multiple extracted poles - L.P. Mospan (Журнал нано- та електронної фізики)
We present the numerical simulation results of the scattering of a plane linearly polarized wave at a multi-aperture frequency-selective surface and two design examples for a spatial band-pass filter with multiple extracted poles. Filters are formed by three consecutively placed perforated screens. Shown, that the screens, elementary cell of which contains a number of different rectangular apertures, provide the appearance of extracted poles on the frequency response of the filter.